Spatial study of environmental vulnerability to earthquakes based on vegetation conditions - Dionysius Otniel Santya Yudhistira (Calamity: A Journal of Disaster Technology and Engineering, 2026)
Background: Earthquakes are among the most destructive natural hazards, causing not only structural damage and loss of life but also long-term environmental degradation and vegetation decline. The ecological dimension of seismic vulnerability has often been overlooked in spatial studies, particularly in tropical regions. This research aims to assess environmental vulnerability to earthquakes based on vegetation conditions along the Opak Fault in the Special Region of Yogyakarta, Indonesia. Methods: The study employs a quantitative–spatial approach using Geographic Information Systems (GIS) to analyze vegetation coverage within three buffer zones at radii of 2 km, 5 km, and 10 km from the active fault line. Secondary data from the Geospatial Information Agency (BIG) and PVMBG were processed to calculate the Environmental Vulnerability Index (EVI) using the ratio of vegetated area to total buffer area, expressed as a percentage. Findings: Results indicate that vulnerability decreases with distance from the fault: 49% (high) for 0–2 km, 45% (high) for 2–5 km, and 40% (moderate) for 5–10 km. The innermost zones, dominated by irrigated rice fields on saturated alluvial soils, exhibit the highest susceptibility to liquefaction and ground shaking. In contrast, areas with greater forest cover show higher ecological resilience. Conclusion: The findings underscore the need to integrate vegetation-based management and Ecosystem-Based Disaster Risk Reduction (Eco-DRR) strategies into local spatial planning to strengthen environmental resilience in seismically active regions. Novelty/Originality of this article: This study uniquely combines GIS-based spatial analysis with vegetation data to assess earthquake vulnerability, highlighting ecological factors often overlooked in seismic risk assessments and informing ecosystem-based disaster risk reduction strategies.